Arabidopsis CER1-LIKE1 Functions in a Cuticular Very-Long-Chain Alkane-Forming Complex - Pascal, Stéphanie (Plant Physiol, 2019)
Plant aerial organs are coated with cuticular waxes, a hydrophobic layer that primarily serves as a waterproofing barrier. Cuticular wax is a mixture of aliphatic very-long-chain molecules, ranging from 22 to 48 carbons, produced in the endoplasmic reticulum of epidermal cells. Among all wax components, alkanes represent up to 80% of total wax in Arabidopsis (Arabidopsis thaliana) leaves. Odd-numbered alkanes and their derivatives are produced through the alkane-forming pathway. Although the chemical reactions of this pathway have been well described, the enzymatic mechanisms catalyzing these reactions remain unclear. We previously showed that a complex made of Arabidopsis ECERIFERUM1 (CER1) and CER3 catalyzes the conversion of acyl-Coenzyme A’s to alkanes with strict substrate specificity for compounds containing more than 29 carbons. To learn more about alkane biosynthesis in Arabidopsis, we characterized the biochemical specificity and physiological functions of a CER1 homolog, CER1-LIKE1. In a yeast strain engineered to produce very-long-chain fatty acids, CER1-LIKE1 interacted with CER3 and cytochrome B5 to form a functional complex leading to the production of alkanes that are of different chain lengths compared to that produced by CER1-containing complexes. Gene expression analysis showed that both CER1 and CER1-LIKE1 are differentially expressed in an organ- and tissue-specific manner. Moreover, the inactivation or overexpression of CER1-LIKE1 in Arabidopsis transgenic lines specifically impacted alkane biosynthesis and wax crystallization. Collectively, our study reports on the identification of a further plant alkane synthesis enzymatic component and supports a model in which several alkane-forming complexes with distinct chain-length specificities coexist in plants.